Non-Albicans Candiduria: An Emerging Threat - Rahul Kumar Goyal,Hiba Sami,Vashishth Mishra,Rajesh Bareja,Rabindra Nath Behara (Journal of Applied Pharmaceutical Science, 2016)
Objective: The incidence of Candida has been on rise worldwide. Clinicians face dilemma in differentiating colonization from true candiduria. The species identification of Candida is important, as non albicans Candida species are increasing in number and more resistant to antifungal drugs. Material and methods: The present study was conducted at a tertiary care teaching hospital of North India with an aim of investigating prevalence of NAC spp. among Candida isolates from urinary tract specimens. Results: A total of 7627 urine samples were analysed in a tertiary care hospital. The Candida isolates (180) were further speciated by Gram stain, culture on sabouraud’s dextrose agar, germ tube test, sugar fermentation test. A total of 180 (2.36%) Candida species were isolated from 7627 urine samples. Among them non albicans Candida species were predominant (66.7%), compared to Candida albicans(33.3%).The rate of isolates of Candida species were more in females, 101 (56.1%) than in males 79 (43.9%). The highest isolation rates of Candida among uropathogens were found in age group above 60 years.The emergence of non-albicans Candida similar to the trends in the western countries should be a cause of concern in our country. Conclusions: NAC spp. have emerged as an important cause of urinary tract infections. Its isolation from clinical specimens can no longer be ignored as nonpathogenic isolate nor can it be dismissed as a contaminant. Proper surveillance of these fungal pathogens is important to improve quality of care in tertiary care setting.
Keywords: Non Albicans Candida,UTI,Candiduria.